Microstructural and Elemental Characterization of TPU/Jute CNFs Nanocomposites via FESEM and EDX Analysis - Nordi, Siti Syazwani; Mhd Noor, Ervina Efzan; Abdul Kadir, Aeslina Binti; Baig, Mirza Farrukh (Ital Publication, 2025)
This study aims to investigate the microstructural and elemental characteristics of thermoplastic polyurethane (TPU) nanocomposites reinforced with jute cellulose nanofibers (CNFs), with the objective of understanding the dispersion behavior and interfacial interactions within the polymer matrix. CNFs were extracted from jute fibers through a chemo-mechanical process involving alkaline treatment, acid hydrolysis, bleaching, and high-energy milling, followed by melt blending with TPU to fabricate nanocomposites at varying filler loadings (1–5 wt%). Field Emission Scanning Electron Microscopy (FESEM) and Energy Dispersive X-ray (EDX) spectroscopy were employed to analyze the surface morphology and elemental distribution of the nanocomposites. The FESEM results revealed that uniform CNF dispersion was achieved up to 4 wt%, beyond which noticeable agglomeration occurred. EDX analysis confirmed the successful incorporation of CNFs and identified performance-enhancing elements such as Si, Ca, Na, and Al in the reinforcement phase. These findings suggest that CNF content strongly influences microstructure and bonding quality, which are key factors for mechanical performance. The novelty of this work lies in its exclusive focus on microstructural and elemental characterization—providing essential insight into filler distribution and matrix compatibility—offering a foundation for optimizing sustainable, high-performance TPU/CNF nanocomposites for advanced industrial applications.